THE CONTINUITY OF THE STUDY ON THETOPIC "COMPLEX NUMBERS" IN SECONDARY SCHOOLS AND IN PEDAGOGICAL UNIVERSITIES OF THE REPUBLIC OF UZBEKISTAN - Bakirov, Tolkinjon (Physical and Mathematical Education, 2021)
Brief descriptions of the problem. In connection with the reforms carried out in the field of education in the Republic of Uzbekistan, the content of secondary education, in particular mathematical education is changing. This article discusses the question of studying succession of the topic "Complex numbers" at school and pedagogical university, and changes in the content of secondary education, in particular mathematical education. In the curriculum of school mathematics of the Republic of Uzbekistan, such new sections as  combinatorics, elements of mathematical logic, complex numbers, elements of probability theories, elements of mathematical statistics, and financial mathematics were introduced. As a result, some topics or their content, the particular topic "Complex numbers", are repeated in the course of university mathematics. It is necessary to develop a methodology for studying newly introduced sections of mathematics, especially some recurring topics, to indicate the levels of assimilation of repetitive concepts by pupils of school and students of university.Materials and methods. During the study, various research methods were applied, namely, the study and analysis of scientific and pedagogical, methodological, mathematical literature and school textbooks in subject of mathematics; analysis of the continual relationships of the section "Complex numbers"; a pedagogical experiment, in which 89(eighty nine) first-year students of Fergana State University were participated, was hold to test the residual knowledge of students on the topic "Complex numbers"; research materials were discussed.Results. In the course of the study, the levels of understanding of educational elements and levels of abstraction characterizing the language of presentation of educational information on the topic “Complex numbers” were proposed.Conclusion. The results obtained can be used by schoolteachers to develop the knowledge and competence of students on the topic of complex numbers, as well as by mathematics teachers in higher educational institutions when choosing a methodology for teaching complex numbers.
Keywords: succession; complex numbers; algebra and number theory; mathematical analysis; theory of analytical functions; level of assimilation; degree of abstraction